Efficacy of Exercise on Depression: A Systematic Review - Mura , Gioia (International Journal of Psychosocial Rehabilitation, 2014)
OBJECTIVES: in the last 30 years, a number of studies have shown that physical activity may reduce depressive symptoms both in healthy populations and in patients diagnosed with MDD. This systematic review of the literature aims to establish the new findings on the effectiveness of exercise on depression. METHODS: the search of significant articles was carried out in PubMed/Medline with the following key words: “exercise”, “physical activity”, “physical fitness”, “depressive disorder”, “depression”, and “depressive symptoms”. Interval was set from January 2000 to December 2012. RESULTS: 46 papers were retrieved by the search. Among the 14 included randomized controlled trials, treatment allocation was adequately conceived in 5 studies, intention-to-treat analysis was performed in 10 studies, and the main outcome assessment was blinded in all but three of the studies. We examined the results of all these trials, finding a small effect of exercise on depression, contaminated by the poor quality of the researches. CONCLUSIONS: in the last 12 years, few progresses were done in showing the efficacy of exercise on depression, due in part to the persistent lack of high quality research, in part to the difficult to establish the real effectiveness of exercise on depressive symptoms. However, there are some promising findings on physical activity combined with antidepressants as an add-on strategy to manage depression, which may be probably more useful in clinical practice